Enunciações docentes sobre o brincar nos processos de formação continuada na educação infantil - Soares, Leticia Cavassana (2017)
This research inserts itself in the field of Early Childhood Education (ECE) focusing on the topic of playing related to teacher continuing formation. As a general goal, it aims to comprehend the teachers’ utterances regarding the act of playing on the formative meetings of an Early Chidhood Education institution. With such goal, it aims to identify the conceptions associated to playing, by investigating the senses produced on the continuing formation meetings, concerning the act of playing, as well as understanding how this act is related to pedagogical practices on the ECE quotidian, parting from listening the teachers’ utterences. Based on Bakhtin’s theoretical-metodological approaches, an exploratory study of quantitative nature is conducted, aiming to accompanying the formative meetings of a Municipal Early Childhood Education Center (Cemei in portuguese) situated in a municipality of Grande Vitória-ES, during the year of 2016. As methodological procedures, observation of the activities of continuing formation were held, as well as interviews with the school principal and pedagogue, applying of questionnaire and moments of reflexive conversations, focusing on the utterances produced along the research development. With the data analysis, the results showed the importance of addressing the question of playing on formative meetings, as these meetings give opportunity to sharing knowledge, ideas, experiences, projects and practices which count playing as part of the educative work done with children. So, considering the challenges in giving rise to the development of teachers who play and, further on, of an institution that plays, conceiving ludism as part of the complex of actions executed in such space, the study points to the relevance of thinking about playing as an action that do not restrict itself to pedagogical practices, but questions, creates tensions and mobilizes new playing practices that recognize playing as an activity that is part of ECE quotidian.